2015
DOI: 10.1557/mre.2015.16
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the structure and structural degradation mechanisms in high-voltage, lithium-manganese–rich lithium-ion battery cathode oxides: A review of materials diagnostics

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 108 publications
0
31
0
Order By: Relevance
“…The (I(006)+I(102))/I(101) ratio (or so called R-factor) informs about the hexagonal ordering of the crystal structure of the electrodes. In practice, a small ratio translates into a good separation in the transition metal and the Li+ respective planes [38,39] yielding to a good hexagonal ordering [40]. With a higher R factor after cycling, it is found that the hexagonal ordering of the initially delithiated electrodes is affected by ageing.…”
Section: Resultsmentioning
confidence: 99%
“…The (I(006)+I(102))/I(101) ratio (or so called R-factor) informs about the hexagonal ordering of the crystal structure of the electrodes. In practice, a small ratio translates into a good separation in the transition metal and the Li+ respective planes [38,39] yielding to a good hexagonal ordering [40]. With a higher R factor after cycling, it is found that the hexagonal ordering of the initially delithiated electrodes is affected by ageing.…”
Section: Resultsmentioning
confidence: 99%
“…1). Considerable work has been applied to the development of new positive electrode materials as discussed by Mohanty et al [25]. The negative electrode is typically formed of carbonaceous materials such as graphite, whereby intercalation compounds can be formed, LiCx (Eqn.…”
Section: Electrochemical Devicesmentioning
confidence: 99%
“…LiNixMnyCo1-x-yO2 (NMC) is a class of cathode material attractive for the electric vehicle applications [36][37][38][39]. NMC is generally comprised of alternating Li and transition-metal layers where the composition of Ni, Mn, and Co can be tuned to optimize the performance in capacity, cyclic rate, electrochemical stability, and lifetime.…”
Section: Introductionmentioning
confidence: 99%